Masjid, Perkembangan, Arsitektur Perkembangan Masjid Besar Ciparay Dan Transformasi Arsitekturnya Dari Neo-Vernakular Ke Modern (1980-2021) - Lutfi Naufal Ihsan; Mardani (Priangan: Journal of Islamic Sundanese Culture, 2026)
The Ciparay Grand Mosque is a sub-district mosque used for Islamic worship and religious practices. This mosque is active in various activities and events. The mosque's facilities from the old to the new show a trend towards improvement. The architectural changes differ from the previous one because the building has experienced damage in various parts. Initially using a neo-vernacular architectural style, it has changed to a modern architectural style. With two contrasting architectures, it must first be discussed to be accepted. The impact of these changes not only affects the mosque building, but also its management. The method used in this study is the historical research method. The steps are heuristics, criticism, interpretation, and historiography. The theory used is Stuart McPhill Hall's representation theory. Architecture is related to the ideas that underlie it. The results of this study are as follows: First, the development of various activities at the Ciparay Grand Mosque is that there is no dominant mass organization; all can use the mosque equally. The imam alternates during Obligatory Prayers and Friday Prayers. Both mosques have undergone significant architectural changes. Originally built in the 1980s, the architecture was neo-vernacular, characterized by a three-tiered pyramid-shaped shingle roof and a predominance of wood. In 2019, the mosque underwent renovations involving various parties. In 2021, the architecture was modern, characterized by tall pillars, a large dome, a predominance of modern materials, and a new lighting system.